Prevalensi gen penyandi resisten Colistin mcr-1 pada isolat Klebsiella pneumoniae dan Escherichia coli Extended-Spectrum Beta-Lactamases (ESBL) di RSUP Sanglah, Bali tahun 2018 - Gusti Ayu Dianti Violentina; Ni Nyoman Sri Budayanti; Ida Sri Iswari (Intisari Sains Medis, 2020)
Background: Antimicrobial resistance (AMR) is a serious threat to health, both human and animal health. Antibiotic resistance in the Enterobacteriaceae family, especially the bacteria Klebsiella pneumoniae and Escherichia coli, is a special focus because it is caused by pathogenic Gram-negative bacteria found in humans. This study aims to study the prevalence of Colistin mcr-1 resistant coding gene in Klebsiella pneumoniae and Escherichia coli Extended-Spectrum Beta-Lactamases (ESBL) isolates in Sanglah Hospital, Bali, in 2018.Methods: This study was conducted in 2 stages, namely examination by PCR and telephone by sequencing. This study's object was the bacteria Klebsiella pneumoniae and Escherichia coli ESBL in clinical isolates of the Clinical Microbiology Laboratory of Sanglah Hospital Denpasar-Bali. Data were analyzed using SPSS version 20 for Windows.Results: The results of this study indicate that the results of clinical examination of 300 isolates, most of the K. pneumoniae and E. coli specimens were found in urine (32.00%), followed by pus (24.00%), sputum (20.00%), blood (12.00%), and others (11.00%). Most of the K. pneumoniae infections were found in sputum (70.49%), pus (52.05%), and blood (70.27%) specimens. Of the 300 isolates obtained from the results, no isolates had the gene encoding colistin mcr-1 resistance in clinical isolates tested molecularly.Conclusion: From the results of this study, it can be concluded that the colistin mcr-1 resistance coding gene was not found in the tested isolates.  Latar Belakang: Antimicrobial resistance (AMR) merupakan ancaman serius di dunia kesehatan baik kesehatan manusia maupun hewan. Resistensi antibiotika pada family Enterobacteriaceae khususnya bakteri Klebsiella pneumoniae dan Escherichia coli menjadi fokus khusus karena keduanya merupakan bakteri Gram negatif patogen yang sering ditemukan pada manusia. Penelitian ini bertujuan untuk mengevaluasi prevalensi gen penyandi resisten Colistin mcr-1 pada isolat Klebsiella pneumoniae dan Escherichia coli Extended-Spectrum Beta-Lactamases (ESBL) di RSUP Sanglah, Bali tahun 2018Metode: Penelitian ini dilakukan dalam 2 tahap yaitu identifikasi dengan PCR dan identifikasi dengan sekuensing. Objek dari penelitian ini ada bakteri Klebsiella pneumoniae dan Escherichia coli ESBL pada isolat klinik Laboratorium Mikrobiologi Klinik RSUP Sanglah Denpasar-Bali. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Hasil penelitian ini menunjukkan bahwa hasil pemeriksaan terhadap 300 isolat klinis sebagian besar specimen K. pneumoniae dan E. coli ditemukan pada urin (32,00%), diikuti dengan pus (24,00%), sputum (20,00%), darah (12,00%), dan lain-lain (11,00%). Sebagian besar infeksi K. pneumoniae ditemukan pada spesimen sputum (70,49%), pus (52,05%), dan darah (70,27%). Dari 300 isolat yang diperiksa didapatkan hasil bahwa tidak ada isolat yang memiliki gen penyandi resistensi colistin mcr-1 pada isolat klinik yang diujikan secara molekuler.Kesimpulan: Dari hasil penelitian ini dapat disimpulkan bahwa gen penyandi resisten colistin mcr-1 tidak ditemukan pada isolat yang diuji